Negative electrode, method for producing same, nonaqueous electrolyte secondary battery comprising negative electrode, and method for producing same
By adding carbon nanotubes to the negative electrode active material layer of the nonaqueous electrolyte secondary battery and adjusting its distribution in the active material layer, the problem of insufficient conductivity of metal-based active material particles such as SiOx is solved, and the circulation characteristics and battery life of the secondary battery are significantly improved.
Patent Information
- Application Number
- CN202411190146.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
In the nonaqueous electrolyte secondary battery, the conductivity of metal-based active substance particles such as SiOx is low, resulting in deterioration of the conductive path and affecting the circulation characteristics of the secondary battery.
Carbon nanotubes are added to the active material layer of the negative electrode, and a good conductive path is formed by adjusting the G/D ratio and average length of the carbon nanotubes. The specific method includes forming the first and second mixtures in a mixture of active material particles, a carbon nanotube and a first binder, and ensuring that the proportion of the carbon nanotubes is more than 40%.
By forming an excellent conductive path, the cycle characteristics of the secondary battery are significantly improved, the input and output resistance is reduced, and the service life of the battery is extended.
Smart Images

Figure CN119542355A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode and a method for producing the same, and a nonaqueous electrolyte secondary battery including the negative electrode and a method for producing the same. Background Art
[0002] The non-aqueous electrolyte secondary battery has a negative electrode including an active material layer. The active material layer may include graphite, SiO x and other active material particles, and fibrous carbon such as carbon nanotubes (for example, Japanese Patent Application Laid-Open No. 2021-99955, etc.). Summary of the invention
[0003] SiO x Compared with graphite, metal active material particles have lower conductivity, and the expansion and contraction accompanying the charge and discharge of the secondary battery are large, so the conductive path formed between the active material particles around is degraded, which easily causes the reduction of the cycle characteristics of the secondary battery. Carbon nanotubes can form a good conductive path by bridging between the active material particles, so they are used to suppress the degradation of the conductive path as described above. However, sometimes even when the active material layer contains carbon nanotubes, the cycle characteristics of the secondary battery will also decline.
[0004] An object of the present disclosure is to provide a negative electrode capable of obtaining a secondary battery having excellent cycle characteristics and a method for producing the same, and a nonaqueous electrolyte secondary battery including the negative electrode and a method for producing the same.
[0005] [1] A negative electrode for a non-aqueous electrolyte secondary battery, comprising an active material layer,
[0006] The active material layer includes active material particles, carbon nanotubes and a first binder.
[0007] The active material particles include metal-based active material particles and carbon-based active material particles.
[0008] The G / D ratio of the carbon nanotubes is 30 or more,
[0009] The average length of the carbon nanotubes determined by analyzing a scanning transmission electron microscope image of the active material layer is 1.4 μm or more,
[0010] The active material layer includes a mixture of the carbon nanotubes and the first binder.
[0011] The mixed body includes a first mixed body formed on at least a portion of the surface of the active material particle, and a second mixed body spanning between two of the active material particles.
[0012] [2] The negative electrode according to [1], wherein the ratio of the carbon nanotubes present in the first mixture and the second mixture to the total amount of the carbon nanotubes in the active material layer, as determined by analyzing the scanning transmission electron microscope image of the active material layer, is 40% or more.
[0013] [3] The negative electrode according to [1] or [2], wherein the metal-based active material particles include a metal selected from Si, SiO x and one or more particles of a complex of Si and C.
[0014] [4] The negative electrode according to any one of [1] to [3], wherein the metal-based active material particles include particles of a composite of Si and C.
[0015] [5] The negative electrode according to any one of [1] to [4], wherein the carbon nanotube is a single-walled carbon nanotube.
[0016] [6] The negative electrode according to any one of [1] to [5], wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.
[0017] [7] The negative electrode according to [6], wherein the active material layer includes a second binder different from the first binder,
[0018] The second adhesive includes styrene-butadiene rubber.
[0019] [8] A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of [1] to [7].
[0020] [9] A method for producing a negative electrode is a method for producing a negative electrode for a non-aqueous electrolyte secondary battery, comprising the following steps:
[0021] The first step of preparing the slurry, and
[0022] a second step of forming an active material layer of the negative electrode using the slurry;
[0023] The slurry contains active material particles, a first binder, carbon nanotubes and water.
[0024] The active material particles include metal-based active material particles and carbon-based active material particles.
[0025] The carbon nanotubes have a G / D ratio of 30 or more.
[0026]
[10] The method for producing a negative electrode according to [9], wherein the first step includes the following steps:
[0027] Step (1b), kneading the active material particles, the first binder, the carbon nanotubes and water in a solid content ratio within a range of 60 to 65 wt % to obtain a kneaded body, and
[0028] In step (1c), water is further added to the kneaded product and the mixture is kneaded.
[0029]
[11] The method for producing a negative electrode according to
[10] , wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.
[0030] The step (1c) includes kneading a second binder with the kneaded product and the water.
[0031] The second adhesive includes styrene-butadiene rubber.
[0032]
[12] The method for producing a negative electrode according to
[10] or
[11] , wherein the first step includes, before the step (1b), a step (1a) of dry-mixing the active material particles and the first binder to obtain a mixture,
[0033] In the step (1b), the mixture, the carbon nanotubes and water are kneaded.
[0034]
[13] The method for producing a negative electrode according to any one of
[10] to
[12] , wherein the kneading in the step (1b) is performed using a stirrer having a stirring blade at a rotation speed of 60 rpm or less.
[0035]
[14] The method for producing a negative electrode according to any one of [9] to
[13] , wherein the carbon nanotubes have a DC resistance of 2000Ω or less at 25°C when prepared as a 0.4 wt% aqueous dispersion.
[0036]
[15] The method for producing a negative electrode according to any one of [9] to
[14] , wherein the metal-based active material particles contain a metal selected from Si, SiO x and one or more particles of a complex of Si and C.
[0037]
[16] The method for producing a negative electrode according to any one of [9] to
[15] , wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.
[0038]
[17] A method for producing a non-aqueous electrolyte secondary battery, comprising the step of producing a negative electrode using the method for producing a negative electrode described in any one of [9] to
[16] .
[0039] The above and other objects, features, aspects and advantages of the present invention will become more apparent from the following detailed description of the present invention when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a scanning transmission electron microscope image of the active material layer of the negative electrode according to the embodiment.
[0041] Figure 2 This is a scanning transmission electron microscope image of an active material layer of a negative electrode according to another embodiment.
[0042] Figure 3 This is a flowchart showing an example of a method for producing a negative electrode according to an embodiment. DETAILED DESCRIPTION
[0043] In this specification, unless otherwise specified, the numerical range of "x to y" includes the upper limit and the lower limit. That is, "x to y" means a numerical range of "above x and below y". A numerical value arbitrarily selected from the numerical range can be used as a new upper limit or lower limit. For example, a new numerical range can be set by arbitrarily combining the numerical values in the numerical range with the numerical values recorded in other parts, tables, or figures in this specification.
[0044] (negative electrode)
[0045] Figure 1 This is a scanning transmission electron microscope image (hereinafter also referred to as a “SEM image”) of the active material layer of the negative electrode according to the embodiment, and shows the active material layer obtained by performing the first step (1) in the negative electrode manufacturing method described later. Figure 2 This is a SEM image of an active material layer of a negative electrode according to another embodiment, and shows the active material layer obtained by performing the first step (2) in the negative electrode production method described later.
[0046] The negative electrode of the present embodiment (hereinafter also referred to as "the present negative electrode") is a negative electrode for a non-aqueous electrolyte secondary battery (hereinafter also referred to as a "secondary battery"), and includes an active material layer. The active material layer includes active material particles, carbon nanotubes (hereinafter also referred to as "CNTs") and a first binder. The active material particles include metal-based active material particles (hereinafter also referred to as "metal-based particles") and carbon-based active material particles (hereinafter also referred to as "carbon-based particles"). The G / D ratio of CNT is greater than 30, and the average length of CNT obtained by analyzing the SEM image of the active material layer is greater than 1.4 μm. The active material layer includes a mixture of CNT and a first binder. The mixture includes a first mixture formed on at least a portion of the surface of the active material particles, and a second mixture spanned between two active material particles.
[0047] The present negative electrode may have an active material layer on a negative electrode current collector. The active material layer may be formed on only one side of the negative electrode current collector or may be formed on both sides. The negative electrode current collector is, for example, a metal foil made of a copper material such as copper or a copper alloy.
[0048] The active material layer contains active material particles for the negative electrode. The active material particles contain metal particles and carbon particles, and may also contain active material particles other than metal particles and carbon particles. Relative to the total amount of active material particles, the total content of carbon particles and metal particles contained in the active material particles may be 90 to 100 weight percent, 90 to 99 weight percent, or 92 to 95 weight percent. As for the content ratio of carbon particles to metal particles in the active material particles, the carbon particles:metal particles (weight ratio) may be 70:30 to 95:5, 80:20 to 92:8, or 85:15 to 95:5.
[0049] When the active material layer is formed on both sides of the negative electrode current collector, the weight per unit area of the active material layer on both sides (both sides combined) may be, for example, 150 to 250 g / m 2 , can be 170~230g / m 2 , can also be 180~210g / m 2 . The weight per unit area of each single side of the negative electrode collector may be, for example, half of the weight per unit area of each of the two sides mentioned above. The thickness per single side of the active material layer may be, for example, 90 to 200 μm, 100 to 180 μm, or 120 to 150 μm. The packing density of the active material layer may be calculated by the following formula, and may be, for example, 1.3 to 1.9 g / cc, 1.4 to 1.8 g / cc, or 1.5 to 1.7 g / cc.
[0050] Packing density [g / cc] = weight per unit area of active material layer [g / m 2 ] / Thickness of active material layer [μm]
[0051] The metal particles contain particles of metal elements such as metal monomers or metal oxides containing an element selected from silicon (Si), tin (Sn), antimony (Sb), bismuth (Bi), titanium (Ti), and germanium (Ge). The metal particles preferably contain a metal selected from Si, SiO x (x=0.5 to 1.5), a composite of Si and C (hereinafter also referred to as "SiC composite"), and Sn, or one or more particles selected therefrom, more preferably Si, SiO x and SiC composite particles. The metal-based particles are more preferably SiC composite particles. The SiC composite is, for example, a composite in which Si is dispersed in a carbon matrix.
[0052] The carbon-based particles preferably include one or more particles selected from carbon materials such as graphite, hard carbon, soft carbon and amorphous coated graphite, or are one or more particles selected therefrom, preferably including graphite particles or being graphite particles. The average particle size D50 of the graphite particles can be 5 to 20 μm, 8 to 10 μm, or 10 to 15 μm. The average particle size D50 in this specification is the particle size at which the frequency starting from the smaller particle size in the volume-based particle size distribution reaches 50%. The volume-based particle size distribution can be measured using a laser diffraction particle size distribution measuring device. The specific surface area (BET) of the graphite particles can be 1.0 to 3.0 m 2 / g, or 1.2 to 2.5 m 2 The specific surface area can be calculated by the BET multipoint method on an adsorption isotherm measured by a gas adsorption method using a fully automatic specific surface area meter or the like.
[0053] CNTs may be single-walled carbon nanotubes (hereinafter also referred to as "SWCNTs") or multi-walled carbon nanotubes such as double-walled carbon nanotubes (DWCNTs). SWCNTs are preferred because they have fewer defects in the CNT structure and are more likely to have a high G / D ratio.
[0054] The G / D ratio of CNT is 30 or more, 40 or more, 50 or more, 30 to 200, 40 to 180, or 50 to 150. The G / D ratio is a value obtained by Raman spectroscopy. In the Raman spectrum of CNT, at 1590 cm -1 The Raman shift observed nearby is known as the G band from graphite, at 1350 cm -1 The Raman shift observed near is called the D band from defects in amorphous carbon or graphite. It can be said that the larger the G / D ratio of the CNT, the higher the crystallinity and the greater the strength. As described below, in the case of using a slurry containing CNTs, active material particles and a first binder to form an active material layer, a strong shear force is sometimes applied to mix the above components in order to improve the dispersibility of the CNTs. By using CNTs with a G / D ratio in the above range, it is possible to prevent the CNTs from being torn apart during the mixing of the above components, thereby shortening the length of the CNTs. As a result, a good conductive path can be formed between the active material particles, thereby improving the cycle characteristics of the secondary battery. The G / D ratio in this specification is the ratio of 1550 to 1650cm in the Raman spectrum of the CNT. -1 The maximum peak intensity in the range of 1300-1400 cm -1 The value calculated by setting the maximum peak intensity in the range of is D. The G / D ratio of CNT can be determined by the procedure described in the examples described later.
[0055] The average length of the CNTs in the active material layer is 1.4 μm or more, 1.5 μm or more, 1.6 μm or more, 1.7 μm or more, 2.0 μm or more, or 2.5 μm or more. The average length of the CNTs can be 1.4 to 5.0 μm, 1.5 to 3.0 μm, or 2.0 to 2.5 μm. As described in the embodiments described below, the average length of the CNTs can be determined by analyzing the SEM images. It is believed that by having CNTs of the above average length in the active material layer, a good conductive path can be formed between the active material particles, which can improve the cycle characteristics of the secondary battery.
[0056] The direct current resistance of the CNT in the active material layer at 25° C. when it is prepared as a 0.4 wt % aqueous dispersion may be within the range described in the negative electrode production method described later.
[0057] The content of CNT in the active material layer may be 0.01 to 1 part by weight, 0.05 to 0.1 part by weight, or 0.1 to 0.5 part by weight relative to 100 parts by weight of the active material particles.
[0058] As the first binder, one or more selected from cellulose-based binders such as carboxymethyl cellulose (hereinafter also referred to as "CMC"), methyl cellulose (hereinafter also referred to as "MC"), hydroxypropyl cellulose, and polyacrylic acid (hereinafter also referred to as "PAA") can be cited. The first binder preferably contains at least one of CMC and PAA, and more preferably contains CMC and PAA. CMC, MC and PAA may be in the form of an acid or in the form of a salt, preferably in the form of a salt. Examples of the salt include alkali metal salts such as potassium and sodium.
[0059] The content of the first binder in the active material layer may be 0.5 to 5 parts by weight, 1 to 4 parts by weight, or 2 to 3 parts by weight relative to 100 parts by weight of the active material particles. When there are two or more first binders, the content of the first binder refers to their total amount.
[0060] A mixture refers to a substance in which CNTs are mixed with a first binder to form a state in which CNTs and the first binder are entangled. A substance in which CNTs are attached to the surface of a layer formed by a first binder is not included in the mixture. The mixture includes a first mixture and a second mixture. In the active material layer, the first mixture and the second mixture may be connected as one, or they may not be one. In addition to the integrated first mixture and second mixture, the first mixture that is not integrated with the second mixture is also included. The two ends of the second mixture spanned between the active material particles can be formed on the surface of the active material particles. In this case, in this specification, in the part of the second mixture that contacts the active material particles, the range of the same diameter as the diameter of the bridge part (the part spanned in a manner connecting two active material particles) is included in the second mixture but not in the first mixture, and the part in contact with the active material particles outside this range is included in the first mixture but not in the second mixture.
[0061] The first mixture can be formed in a manner that directly contacts the surface of the active material particles. The first mixture only needs to be formed on at least a portion of the surface of the active material particles. For example, it can be formed in a manner that is dispersed on the surface of the active material particles, or it can be formed in a manner that covers the entire surface of the active material particles. By having the first mixture, it is easy to ensure the electrical connection point between the active material particles and the CNTs, compared to the case where the CNTs are arranged on the surface of the first binder layer formed on the surface of the active material particles, and therefore it is easy to reduce the input-output resistance when the negative electrode is used in a secondary battery.
[0062] like Figure 1 and Figure 2 As shown by the dotted circle, the second mixture is formed in a manner of bridging between two active material particles. Both ends of the second mixture can be formed in a manner of directly contacting the surfaces of the two active material particles. Since the second mixture can form a conductive path between the active material particles, the secondary battery using the present negative electrode can have excellent cycle characteristics.
[0063] The active material layer including the first mixture and the second mixture can be obtained by adjusting the order of mixing CNTs, the solid content concentration when mixing CNTs, and other conditions when preparing a slurry for forming the active material layer (described later).
[0064] In the active material layer, in addition to CNTs present in the form of a mixture, CNTs not present in the form of a mixture, i.e., not mixed with the first binder, are also included. The ratio of CNTs present in the first mixture and the second mixture to the total amount of CNTs in the active material layer (hereinafter also referred to as "CNT ratio") is preferably 40% or more, more preferably 45% or more, and may be 50% or more. The CNT ratio is preferably 40 to 90%, 45 to 80%, or 50 to 70%. By making the CNT ratio within the above range, it is easy to ensure the electrical connection points between the active material particles and the CNTs, so that the input and output resistance when the negative electrode is used in a secondary battery can be further reduced. As described in the embodiments described later, the CNT ratio can be determined by analyzing the SEM image of the active material layer.
[0065] As a method for adjusting the CNT ratio to the above, there can be cited a method of adjusting the order of mixing the CNTs, the solid content concentration when mixing the CNTs, and other conditions when preparing the slurry for forming the active material layer. In the active material layer obtained by performing the first step (1) described later ( Figure 1 ), it is easy to adjust the CNT ratio to the above range, and the entanglement between the CNTs in the second mixture and the first binder is also easy to increase. On the other hand, in the active material layer obtained by performing the first step (2) described later ( Figure 2 ), it is difficult to adjust the CNT ratio to the above range, and the entanglement between the CNTs in the second mixture and the first binder tends to decrease.
[0066] In addition to the active material particles, CNTs and the first binder, the active material layer may also include a second binder other than the first binder and a conductive material other than CNTs. When the first binder includes at least one of CMC and PAA, or at least one of CMC and PAA, the second binder may include at least one of styrene-butadiene rubber (SBR) and polyvinyl alcohol (PVA), preferably SBR. As conductive materials other than CNTs, carbon materials such as carbon black (e.g., acetylene black, Ketjen black), coke, and activated carbon can be cited.
[0067] (Method for manufacturing negative electrode)
[0068] Figure 3 : is a flowchart showing a method for manufacturing a negative electrode according to an embodiment. The method for manufacturing a negative electrode according to this embodiment can manufacture a negative electrode for a secondary battery, and can also manufacture the present negative electrode. The method for manufacturing a negative electrode includes: a first step of preparing a slurry, and a second step of forming an active material layer of the negative electrode using the slurry ( Figure 3 The slurry includes active material particles, a first binder, CNTs, and water. The active material particles include metal particles and carbon particles, and the G / D ratio of the CNTs is 30 or more.
[0069] The slurry prepared in the first step includes active material particles, a first binder, CNTs, and water. The solid content ratio of the slurry can be 35 to 55% by weight, 40 to 50% by weight, or 43 to 48% by weight. Examples of the metal particles and carbon particles include the above-mentioned materials. Examples of the first binder include the above-mentioned materials.
[0070] As CNT, the above-mentioned materials can be cited, preferably SWCNT. The G / D ratio of CNT can be in the range described above. When CNT is made into a 0.4 wt% aqueous dispersion, the DC resistance at 25°C is preferably 2000Ω or less, 1900Ω or less, 1800Ω or less, 1700Ω or less, 500-2000Ω, 700-1900Ω, 1000-1800Ω, or 1000-1700Ω. CNTs having a DC resistance in the above range have excellent conductivity, so they can form a good conductive path between the active material particles in the active material layer. The above DC resistance can be measured according to the steps described in the embodiments described later.
[0071] The slurry may further contain a second binder, and may contain a conductive material other than CNT. Examples of the second binder and the conductive material include the above-mentioned materials.
[0072] The first step may be the first step (1) or the first step (2) described later. By making the first step the first step (1) or the first step (2), it is easy to obtain a negative electrode having a G / D ratio of 30 or more, an average length of CNTs in the active material layer of 1.4 μm or more, and an active material layer containing the first mixture and the second mixture. From the perspective of obtaining an active material layer with the above-mentioned CNT ratio, the first step is preferably the first step (1).
[0073] The second step is a step of forming an active material layer using the slurry prepared in the first step. The second step may include applying the slurry on the negative electrode collector to form a coating layer, and drying the coating layer, and may further include a step of compressing the dried coating layer. As the negative electrode collector, the above-mentioned materials can be cited.
[0074] The first step (1) may include: a step (1b) of kneading active material particles, a first binder, CNTs and water in a solid content ratio range of 60 to 65% by weight to obtain a first kneaded body (kneaded body); and a step (1c) of further adding water to the first kneaded body for kneading. In step (1b), step (1c) is performed after the active material particles, the first binder and CNTs are kneaded at a larger solid content ratio. As a result, the first binder and CNTs are fully entangled, so it is easy to adjust the proportion of CNTs present in the first mixture to the above range, and it is easy to ensure the electrical connection points between the active material particles and the CNTs. In addition, the entanglement between the CNTs and the first binder in the second mixture is also easy to increase. Therefore, by using a negative electrode manufactured in a manufacturing method including the first step (1), it is easy to have excellent cycle characteristics and obtain a secondary battery with reduced input and output resistance.
[0075] The solid content ratio in step (1b) (solid content ratio of the first kneaded body) is preferably 60 to 65% by weight, 61 to 65% by weight, 62 to 65% by weight, or 63 to 64% by weight. By making the solid content ratio in step (1b) within the above range, it is easy to adjust the CNT ratio to the above range, and the entanglement between the CNTs in the second mixture and the first binder is also easy to increase.
[0076] In the first step (1), before the step (1b), a step (1a) may be included in which the active material particles and the first binder are dry-mixed to obtain a mixture. When the first step (1) includes the step (1a), the step (1b) may be obtained by kneading the mixture, CNTs and water to obtain a first kneaded body. The first step (1) may include a step (1c) of further adding water to the first kneaded body for kneading. The step (1c) may include a step of kneading the second binder together with the first kneaded body and water. In this case, there is no particular restriction on the order of kneading the first kneaded body, the second binder and water in the step (1c), and they may be kneaded together, or the first kneaded body and water may be kneaded first, and then the second binder may be added for kneading.
[0077] The first step (1) can be carried out using a stirrer with a stirring blade. There is no particular limitation on the rotation speed of the stirring blade in each step included in the first step (1). The rotation speed of the stirring blade in the step (1b) can be 60 rpm or less, 50 rpm or less, 40 rpm, 10 to 60 rpm, 20 to 50 rpm, or 30 to 40 rpm. Since CNTs with a large G / D ratio are used in the manufacturing method of this embodiment, even if the mixing of the step (1b) is carried out at the above-mentioned rotation speed, the CNTs can be prevented from being torn apart. As a result, a good conductive path can be formed in the active material layer, thereby improving the cycle characteristics of the secondary battery. The mixing time in the step (1b) can be 10 to 200 min, 70 to 150 min, or 80 to 120 min.
[0078] The rotation speed of the stirring blade in step (1c) may be 50 rpm or less, 40 rpm or less, 30 rpm or less, 5 to 50 rpm, 10 to 40 rpm, or 20 to 30 rpm. The kneading time in step (1c) may be, for example, 10 to 180 min, 20 to 150 min, or 30 to 120 min.
[0079] The first step of the negative electrode manufacturing method can also be performed by the first step (2) described below instead of the above-mentioned first step (1). The first step (2) includes: a step (2b) of kneading the active material particles, the first binder and water to obtain a second kneaded body, a step (2c) of kneading the second kneaded body and CNTs to obtain a third kneaded body, and a step (2d) of adding water to the third kneaded body for kneading. In the first step (2), after the active material particles and the first binder are kneaded, CNTs are added for kneading, so that CNTs can be dispersed in a short time. As a result, compared with the case of manufacturing by the first step (1), the first binder is more likely to adhere to the surface of the active material particles than when mixed with CNTs, and CNTs are more likely to adhere to the first binder on the surface of the active material particles. Therefore, it is difficult to adjust the ratio of CNTs present in the first mixture and the second mixture to the above-mentioned range, and the entanglement of CNTs and the first binder in the first mixture and the second mixture is also likely to become smaller. Therefore, the input / output resistance of the negative electrode manufactured by the first step (2) is more likely to be larger than that of the negative electrode manufactured by the first step (1).
[0080] The solid content ratio in step (2b) (solid content ratio of the second kneaded product) is preferably 60 to 65% by weight, 61 to 65% by weight, 62 to 65% by weight, or 63 to 64% by weight.
[0081] In the first step (2), before the step (2b), the step (2a) of dry-mixing the active material particles and the first binder to obtain a mixture may be included. When the first step (2) includes the step (2a), the step (2b) may be performed by kneading the mixture with water to obtain a second kneaded body.
[0082] The solid content ratio in step (2c) (solid content ratio of the third kneaded product) is, for example, greater than 55% by weight and less than 60% by weight, and may be 56 to 59% by weight, or 57 to 58% by weight.
[0083] Step (2d) may include a step of kneading the second binder together with the third kneaded product and water. The kneading order of the third kneaded product, the second binder and water in step (2d) is not particularly limited, and they may be kneaded together, or the third kneaded product and water may be kneaded first, and then the second binder may be added and kneaded.
[0084] The first step (2) can be carried out using a stirrer with a stirring blade. The rotation speed of the stirring blade in each step included in the first step (2) is not particularly limited. For example, the rotation speed of the stirring blade in the step (2b) can be 10 to 65 rpm, 20 to 60 rpm, or 30 to 55 rpm. The kneading time in the step (2b) can be, for example, 10 to 200 min, 70 to 150 min, or 80 to 120 min.
[0085] The rotation speed of the stirring blade in step (2c) may be 20 to 65 rpm, 30 to 60 rpm, or 40 to 55 rpm. The kneading time in step (2c) may be, for example, 5 to 60 min, 10 to 30 min, or 10 to 20 min.
[0086] The rotation speed of the stirring blade in step (2d) may be 5 to 50 rpm, 10 to 40 rpm, or 20 to 30 rpm. The kneading time in step (2d) may be, for example, 10 to 90 min, 15 to 60 min, or 30 to 45 min.
[0087] (Non-aqueous electrolyte secondary battery)
[0088] The non-aqueous electrolyte secondary battery of the present embodiment (hereinafter also referred to as "the present battery") comprises the present negative electrode, and generally comprises an electrode body containing the present negative electrode and a non-aqueous electrolyte. The present battery may have a battery case for accommodating the electrode body and the non-aqueous electrolyte. The battery case may include an outer casing having an opening, and a sealing plate for sealing the opening. The outer casing and the sealing plate are preferably made of metal, and may be formed using aluminum, an aluminum alloy, iron or an iron alloy, and may be formed using an aluminum laminate film, for example. A resin sheet serving as an electrode holder may be configured between the electrode body and the outer casing.
[0089] The electrode body may include the present negative electrode, the positive electrode and the separator. In the electrode body, the active material layer of the present negative electrode and the positive electrode active material layer of the positive electrode are opposed to each other via the separator. The electrode body may be a laminated type in which the present negative electrode, the positive electrode and the separator are laminated, or a wound type in which a laminated body in which the present negative electrode, the positive electrode and the separator are laminated is wound.
[0090] The positive electrode generally has a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector is, for example, a metal foil made of aluminum materials such as aluminum and aluminum alloys. The positive electrode active material layer contains positive electrode active material particles, and may further contain a conductive material and a binder. Examples of positive electrode active material particles include layered or spinel lithium transition metal oxides (e.g., LiNiCoMnO2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 O4, LiCrMnO4, LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) particles. The lithium transition metal oxide may be a lithium nickel cobalt manganese composite oxide (NCM). As the conductive material, for example, carbon materials such as fibrous carbon (CNT (SWCNT, DWCNT)), carbon black (such as acetylene black, Ketjen black), coke, activated carbon, etc. may be cited. As the binder, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE) and SBR may be cited.
[0091] The spacer has a substrate, and at least one side of the substrate may have a functional layer. The substrate may be a porous sheet such as a film and non-woven fabric composed of a resin such as polyethylene, polypropylene, polyester, cellulose, polyamide, etc. The substrate may have a single-layer structure or a multi-layer structure. As the functional layer, for example, an adhesive layer and a heat-resistant layer may be cited, and one or both of these may be included. The adhesive layer may be formed, for example, by an adhesive. The heat-resistant layer may include, for example, a filler and a binder.
[0092] The non-aqueous electrolyte preferably contains a supporting salt in a non-aqueous solvent such as an organic solvent. As supporting salts, LiPF6, LiBF4, LiClO4, LiFSO3, LiBOB (lithium bis(oxalate)borate) etc. can be cited. The non-aqueous electrolyte can include one or more supporting salts of these. As non-aqueous solvents, for example, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate (PC), butylene carbonate (BC) and diethyl carbonate (DEC) etc. can be cited. The non-aqueous electrolyte can include one or more non-aqueous solvents of these.
[0093] (Method for producing non-aqueous electrolyte secondary battery)
[0094] The manufacturing method of the battery includes the step of manufacturing the negative electrode by the manufacturing method of the negative electrode. The manufacturing method of the battery may further include the step of obtaining an electrode body using the negative electrode, the positive electrode and the separator, and the step of accommodating the electrode body and the non-aqueous electrolyte in a battery case.
[0095] Example
[0096] The present disclosure will be described in more detail below with reference to Examples and Comparative Examples.
[0097] [Example 1]
[0098] (Production of negative electrode: produced by the first step (1))
[0099] Graphite particles were used as carbon particles, and Si and C composite particles (SiC composite particles) were used as metal particles. The average particle size D50 of the graphite particles was 17 μm, and the specific surface area (BET) of the graphite particles was 2.2 m 2 / g. The CNT had the G / D ratio shown in Table 1 and the DC resistance when prepared as a 0.4 wt% aqueous dispersion. The slurry (1) was prepared by the following procedure using a stirrer (HIVIS MIX 2P-1 manufactured by PRIMIX).
[0100] First, carbon particles, metal particles, CMC and PAA as the first binder are dry-mixed to obtain a mixture (step (1a)). Next, CNT (a water-soluble paste with a solid content ratio of 1% by weight) and water are added to the mixture to make the solid content ratio 64% by weight, and kneaded at a stirrer speed of 50 rpm for 90 minutes to obtain a first kneaded body (step (1b)). Water is further added to the first kneaded body, and after kneading at a stirrer speed of 30 rpm for 30 minutes, SBR is added as a second binder, and kneaded at a stirrer speed of 30 rpm for 5 minutes (step (1c)) to obtain a slurry (1) with a solid content ratio of 46% by weight. The mixing ratio of the slurry (1) is graphite particles: SiC composite particles: CNT: CMC: PAA: SBR = 91:9:0.05:1:1:1 (weight ratio).
[0101] The slurry (1) obtained above was applied to both sides of a copper foil with a thickness of 8 μm as a negative electrode current collector, dried, and compressed to obtain a negative electrode (1). The unit area weight of the active material layer of the negative electrode (1) (the total unit area weight of both sides) was 195 g / m 2 The thickness of the active material layer (per single surface) was 130 μm, and the packing density of the active material layer was 1.52 g / cc. The active material layer of the negative electrode (1) contained a first mixture and a second mixture.
[0102] (Production of positive electrode)
[0103] Lithium nickel cobalt manganese composite oxide (NCM) as positive electrode active material particles, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder are used in a ratio of positive electrode active material particles: AB: PVdF = 100: 1: 1 (weight ratio), and they are mixed with N-methylpyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry is applied on an aluminum foil with a thickness of 15 μm as a positive electrode collector, dried, and compressed to obtain a positive electrode.
[0104] (Fabrication of non-aqueous electrolyte secondary battery)
[0105] Leads are installed on the negative electrode and the positive electrode obtained in the above, respectively, and the negative electrode and the positive electrode are stacked with a separator to obtain an electrode body. The electrode body is inserted into an outer body composed of an aluminum laminate sheet and a non-aqueous electrolyte is injected. The opening of the outer body is sealed to obtain a test battery (laminated battery) (1). The non-aqueous electrolyte uses a solution prepared by dissolving LiPF6 as a lithium salt in a mixed solvent at a concentration of 1 mol / L. The mixed solvent contains ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of EC:EMC:DMC=20:40:40.
[0106] [Example 2]
[0107] (Production of negative electrode: produced through the first step (2))
[0108] The slurry (2) was prepared according to the following steps to obtain the negative electrode (2). In this example, the same carbon particles, metal particles, CNTs, first binder, second binder and agitator as those used in the preparation of the negative electrode in Example 1 were used.
[0109] First, carbon particles (graphite particles), metal particles (SiC composite particles), and the first binder (CMC and PAA) are dry-mixed to obtain a mixture (process (2a)). Then, water is added to the mixture so that the solid content ratio is 64% by weight, and the mixture is kneaded at a stirrer speed of 50 rpm for 90 minutes to obtain a second kneaded body (process (2b)). Next, CNT (a water-soluble paste with a solid content ratio of 1% by weight) is added to the second kneaded body so that the solid content ratio is 54% by weight, and the mixture is kneaded at a stirrer speed of 50 rpm for 15 minutes to obtain a third kneaded body (process (2c)). Water is further added to the third kneaded body, and after kneading at a stirrer speed of 30 rpm for 30 minutes, the second binder (SBR) is added, and the mixture is kneaded at a stirrer speed of 30 rpm for 5 minutes (process (2d)) to obtain a slurry (2) with a solid content ratio of 46% by weight. A negative electrode (2) was obtained by following the procedure for producing the negative electrode of Example 1 except that the slurry (2) was used instead of the slurry (1). The active material layer of the negative electrode (2) contained the first mixture and the second mixture.
[0110] (Fabrication of non-aqueous electrolyte secondary battery)
[0111] A test battery (2) was obtained according to the procedure for producing a non-aqueous electrolyte secondary battery of Example 1 except that the negative electrode (2) was used instead of the negative electrode (1).
[0112] [Comparative Example 1]
[0113] A negative electrode (c1) and a test cell (c1) were obtained according to the procedure described in Example 1, except that CNTs having a G / D ratio shown in Table 1 and a DC resistance when prepared as a 0.4 wt % aqueous dispersion were used instead of the CNTs used in Example 1.
[0114] [Comparative Example 2]
[0115] A negative electrode (c2) and a test cell (c2) were obtained according to the procedure described in Example 2, except that CNTs having a G / D ratio shown in Table 1 and a DC resistance when prepared as a 0.4 wt % aqueous dispersion were used instead of the CNTs used in Example 2.
[0116] [Determination of G / D ratio of CNT]
[0117] The CNT dispersion was separated on a cover glass and irradiated with a laser beam with an excitation wavelength of 532 nm in a range of 300 μm in diameter using a Raman microscope (manufactured by Horiba, Ltd.) to obtain a Raman spectrum. -1 The maximum peak intensity in the range of 1300-1400 cm -1 The maximum peak intensity in the range of was set as D, and the G / D ratio was calculated. The results are shown in Table 1.
[0118] [Measurement of DC resistance of CNT]
[0119] A 0.4 wt% aqueous dispersion of CNT (solid content ratio 1 wt%) was injected into the measuring container of the LCR tester and the test fixture (made by Hioki Electric) and left to stand for 24 hours. Thereafter, AC impedance was measured at a measuring frequency of 4 Hz to 10 MHz at 25°C, and DC resistance (DCR) was measured using a specialized analysis system. The results are shown in Table 1.
[0120] [Determination of average CNT length and CNT ratio]
[0121] (Acquisition of SEM images)
[0122] The surface of the active material layer of the negative electrode was confirmed by using a scanning transmission electron microscope (SEM, manufactured by Hitachi High-Tech) at an accelerating voltage of 1 kV and a SEM image with a visual field of 9×7 μm.
[0123] (Determination of the average length of CNT)
[0124] Use image software to paint the CNT in the above SEM image into a line, measure the circumference of the line, and use half of the value as the length of the CNT. Since CNT has an extremely long aspect ratio relative to its diameter, the effect of the width of the line on the circumference can be ignored. The length of the CNT is determined for all CNTs in the above SEM image, and its average value is used as the average length of the CNT. The results are shown in Table 1. It should be noted that the average length of the CNTs in Comparative Examples 1 and 2 is not shown. It can be considered that since the G / D ratio of the CNTs used in Comparative Examples 1 and 2 is small, the CNTs become shorter during the preparation of the slurry and are difficult to observe in the SEM image.
[0125] (Determination of CNT ratio)
[0126] The ratio [%] of CNTs present in the first mixture and the second mixture relative to all CNTs in the SEM image obtained above (CNT ratio [%]) was calculated according to the following formula.
[0127] CNT ratio [%] = (area of CNTs present in the first mixture and the second mixture in the SEM image / area of all CNTs in the SEM image) × 100
[0128] [Evaluation of initial efficiency]
[0129] Under an environment of 25°C, the test battery was charged at a current value of 0.05C (CC charge) to 4.2V, and then discharged at a current value of 0.05C (CC discharge) to 2.5V for one cycle. The initial efficiency [%] was calculated from the discharge capacity of the first cycle and the charge capacity of the first cycle according to the following formula. The results are shown in Table 1.
[0130] Initial efficiency [%] = (discharge capacity of the first cycle / charge capacity of the first cycle) × 100
[0131] [Evaluation of input and output resistance]
[0132] (Calculation of input resistance)
[0133] Under 25°C environment, the test battery was charged at a current value of 0.33C to a charge rate (SOC) of 50%, and then charged at a current value of 0.33C by constant current and constant voltage charging (CCCV) to a charge rate of 50%, and then stopped for 30 minutes. After that, the input resistance was calculated by measuring the IV (current and voltage) when charging at a current value of 0.2C for 10s. The results are shown in Table 1.
[0134] (Calculation of output resistance)
[0135] Under 25°C environment, the test battery was charged at a current value of 0.33C to a charge rate (SOC) of 50%, and then charged at a current value of 0.33C by constant current and constant voltage charging (CCCV) to a charge rate of 50%, and then stopped for 30 minutes. Thereafter, the output resistance was calculated by measuring the IV (current and voltage) when discharged at a current value of 0.2C for 10s. The results are shown in Table 1.
[0136] [Evaluation of cycle characteristics]
[0137] Under a 25°C environment, the test battery was charged to 4.2V by constant current and constant voltage charging (CCCV) at a current value of 0.33C, and then discharged (CC discharge) at a current value of 0.33C to 2.5V. This charge and discharge was regarded as one cycle, and the charge and discharge were repeated. According to the following formula, the discharge capacity of the 100th cycle relative to the discharge capacity of the first cycle was calculated as the capacity retention rate [%]. The results are shown in Table 1.
[0138] Capacity retention rate [%] = (discharge capacity at the 100th cycle / discharge capacity at the 1st cycle) × 100
[0139] [Table 1]
[0140] Example 1 Example 2 Comparative Example 1 Comparative Example 2 negative electrode (1) (2) (c1) (c2) Slurry (1) (2) (c1) (c2) Step 1 (1) (2) (1) (2) CNT G / D Ratio 69.19 69.19 1.30 1.30 DC resistance [Ω] 1645 1645 2888 2888 Average length [μm] 1.57 2.63 - - <![CDATA[Ratio of CNT *1 [%]]]> 48 19.6 - - Test battery (1) (2) (c1) (c2) Initial efficiency [%] 99.6 99.6 99.7 99.7 Input resistance [Ω] 0.091 0.096 0.101 0.103 Output resistance [Ω] 0.093 0.097 0.103 0.105 Capacity maintenance rate [%] 96.25 96.42 82.83 83.67
[0141] *1: Ratio of CNTs in the first and second mixtures in the SEM image
[0142] Although the embodiments of the present invention have been described, the embodiments disclosed herein are illustrative in all aspects and should not be construed as limiting. The scope of the present invention is indicated by the scope of the claims, and is intended to include all changes within the meaning and scope equivalent to the scope of the claims.
Claims
1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising an active material layer, The active material layer includes active material particles, carbon nanotubes and a first binder. The active material particles include metal-based active material particles and carbon-based active material particles. The G / D ratio of the carbon nanotubes is greater than 30, The average length of the carbon nanotubes determined by analyzing a scanning transmission electron microscope image of the active material layer is 1.4 μm or more, The active material layer includes a mixture of the carbon nanotubes and the first binder, The mixed body includes a first mixed body formed on at least a portion of the surface of the active material particles, and a second mixed body spanning between two of the active material particles.
2. The negative electrode according to claim 1, wherein The ratio of the carbon nanotubes present in the first mixture and the second mixture relative to the total amount of the carbon nanotubes in the active material layer, determined by analyzing the scanning transmission electron microscope image of the active material layer, is 40% or more.
3. The negative electrode according to claim 1, wherein The metal active material particles include Si, SiO x and one or more particles of a composite of Si and C.
4. The negative electrode according to claim 1, wherein The metal-based active material particles include particles of a composite of Si and C.
5. The negative electrode according to claim 1, wherein The carbon nanotubes are single-layer carbon nanotubes.
6. The negative electrode according to claim 1, wherein The first binder is at least one of carboxymethyl cellulose and polyacrylic acid.
7. The negative electrode according to claim 6, wherein The active material layer includes a second binder different from the first binder, The second adhesive includes styrene-butadiene rubber. 8 . A non-aqueous electrolyte secondary battery comprising the negative electrode according to claim 1 .
9. A method for manufacturing a negative electrode, which is a method for manufacturing a negative electrode for a non-aqueous electrolyte secondary battery, comprising the following steps: The first step of preparing the slurry, and a second step of forming an active material layer of the negative electrode using the slurry, The slurry contains active material particles, a first binder, carbon nanotubes and water. The active material particles include metal-based active material particles and carbon-based active material particles. The carbon nanotubes have a G / D ratio of 30 or more.
10. The method for manufacturing a negative electrode according to claim 9, wherein: The first step includes the following steps: Step (1b), kneading the active material particles, the first binder, the carbon nanotubes and water in a solid content ratio within a range of 60 to 65 wt % to obtain a kneaded body, and In step (1c), water is further added to the kneaded mixture and the mixture is kneaded.
11. The method for manufacturing a negative electrode according to claim 10, wherein: The first binder is at least one of carboxymethyl cellulose and polyacrylic acid, The step (1c) includes kneading a second binder together with the kneaded body and the water. The second adhesive includes styrene-butadiene rubber.
12. The method for manufacturing a negative electrode according to claim 10, wherein: The first step includes, before the step (1b), a step (1a) of dry-mixing the active material particles and the first binder to obtain a mixture, In the step (1b), the mixture, the carbon nanotubes and water are kneaded.
13. The method for manufacturing a negative electrode according to claim 12, wherein: The kneading in the step (1b) is performed using a stirrer having a stirring blade, with the rotation speed of the stirring blade being 60 rpm or less.
14. The method for manufacturing a negative electrode according to claim 9, wherein: When the carbon nanotubes are prepared as a 0.4 wt% aqueous dispersion, the direct current resistance at 25° C. is 2000 Ω or less.
15. The method for manufacturing a negative electrode according to claim 9, wherein: The metal active material particles include Si, SiO x and one or more particles of a composite of Si and C.
16. The method for manufacturing a negative electrode according to claim 9, wherein: The first binder is at least one of carboxymethyl cellulose and polyacrylic acid. 17 . A method for producing a nonaqueous electrolyte secondary battery, comprising the step of producing a negative electrode by the method for producing a negative electrode according to claim 9 .
Citation Information
Patent Citations
Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
JP2021099955A